Is patient-centred care for women a priority for policy-makers? Content analysis of government policies - Anna R. Gagliardi; Sheila Dunn; Angel M. Foster; Sherry L. Grace; Nazilla Khanlou; Donna E. Stewart; Sharon E. Straus (BMC, 2020)
Abstract Background Considerable research shows that women experience gendered disparities in healthcare access and quality. Patient-centred care (PCC) could reduce inequities by addressing the patient's clinical and personal needs. Healthcare policies can influence service delivery to optimise patient outcomes. This study assessed whether and how government policies recognise and promote PCC for women (PCCW). Methods We analysed the content of English-language policies published in Canada from 2010 to 2018 on depression and cardiac rehabilitation - conditions featuring known gendered inequities - that were identified on government websites. We extracted data and used summary statistics to enumerate mentions of PCC and women's health. Results We included 30 policies (20 depression, 10 cardiac rehabilitation). Of those, 20 (66.7%) included any content related to PCC (median 1.0, range 0.0 to 5.0), most often exchanging information (14, 46.7%) and making decisions (13, 43.3%). Less frequent domains were enabling self-management (8, 26.7%), addressing emotions (6, 20.0%) and fostering the relationship (4, 13.3%). No policies included content for the domain of managing uncertainty. A higher proportion of cardiac rehabilitation guidelines included PCC content. Among the 30 policies, 7 (23.3%) included content related to at least one women's health domain (median 0.0, range 0.0 to 3.0). Most frequently included were social determinants of health (4, 13.3%). Fewer policies mentioned any issues to consider for women (2, 28.6%), issues specific to subgroups of women (2, 28.6%) or distinguished care for women from men (2, 28.6%). No policies included mention of abuse or violence, or discrimination or stigma. The policies largely pertained to depression. Despite mention of PCC or women's health, policies offered brief, vague guidance on how to achieve PCCW; for example, "Patients value being involved in decision-making" and "Women want care that is collaborative, woman- and family-centered, and culturally sensitive." Conclusions Despite considerable evidence of need and international recommendations, most policies failed to recognise gendered disparities or promote PCC as a mitigating strategy. These identified gaps represent opportunities by which government policies could be developed or strengthened to support PCCW. Future research should investigate complementary strategies such as equipping policy-makers with the evidence and tools required to develop PCCW-informed policies.